An Investigation into the Performance of an Ambidextrously Balanced Innovator and Its Relatedness to Open Innovation - Shinhyung Kang; JungTae Hwang (Journal of Open Innovation: Technology, Market and Complexity, 2019)
This study investigated the relationship between open innovation and the radicalness of innovation. The balance between radical and incremental innovation is an essential part of the ambidextrous use of explorative and exploitative strategies, and this study assumed that open innovation is usually interlinked with explorative strategies and is thus related to radical innovation performance. Accordingly, following an empirical investigation, we demonstrate that the balance of open innovation firms is slightly skewed toward explorative radical innovation. Using the Korean version of the community innovation survey, we show that the relative radicalness that is projected on innovation output exhibits an inverted-U curve. Furthermore, the curve shifts based on the level of inbound open innovation. Our results suggest that there is an ambidextrous balance between radical and incremental innovation while implementing open innovation. In addition, the research results imply that firms placing greater weight on explorative radical innovations need to consider in-depth open innovation strategies.